A study on maternal and perinatal risk factors of cerebral palsy among children attending a cerebral palsy clinic in Visakhapatnam - Soumya, V.; Madhavi, K. V. Phani; Madhavi, B. Devi (International Journal Of Community Medicine And Public Health, 2017)
Background: Cerebral palsy (CP) is a disorder of movement and posture, defined as an “umbrella term covering a group of non-progressive, but often changing, motor impairment syndromes secondary to lesions or anomalies of the brain arising in the early stages of its development”. Risk factors for CP include maternal infection, placental insufficiency, gestational diabetes, pregnancy induced hypertension, instrumental delivery, low birth weight, hypoxic ischemic injury, hyperbilirubinemia, metabolic abnormalities (hypoglycemia). The families are affected psychologically, financially and socially. It also imposes burden on national health system. The objective of the study was to study the distribution of maternal and perinatal risk factors of cerebral palsy among children attending a cerebral palsy clinic in Visakhapatnam. Methods: A retrospective cohort study was conducted by eliciting history from the mothers of 90 cerebral palsy children who were treated in cerebral palsy clinic, Visakhapatnam, Andhra Pradesh, India for a period of 6 months in 2016. After taking consent, data was collected using a pretested questionnaire. Detailed history was taken from the mothers of 90 cerebral palsy children regarding the period of gestation at which the child was born (preterm or full term), any previous history of pre-term delivery or abortions and neonatal complications was obtained from the care givers. Data was entered into MS-excel sheet and analysed by using SPSS Trial Version 20. Results: Total numbers of study subjects were 90, out of which 58 were boys and 32 were girls. Around 38% of study subjects were born out of consanguineous marriage. As per the records available, only 7% of mothers had gestational diabetes. It was found that 13% study subjects were preterm, 22% had low birth weight, 24% had perinatal hypoglycaemia, 33% had neonatal jaundice and 33% had birth asphyxia. Conclusions: Consanguinity, birth asphyxia, neonatal jaundice are found to be the important risk factors for Cerebral Palsy in our study which can be avoided by improving maternal and paediatric health services.